A Direct Torque Control Scheme With Integrated Commutation Torque Ripple Reduction for BLDC Motor Drives With Open-End Windings - Hari Krishna U; Rajeevan P P (IEEE Open Journal of Power Electronics)
This article presents a direct torque control (DTC) scheme with an integrated switching strategy to reduce commutation torque ripple in a dual inverter-fed three-phase BLDC motor with open-end stator windings. The proposed scheme covers both low- and high-speed operation, utilizing voltage space vector structures in two-phase and three-phase conduction modes. Analysis shows that utilizing three-phase conducting voltage vectors during the commutation interval significantly reduces torque ripple compared to the DTC scheme using only two-phase conducting voltage space vectors. The two-phase conducting voltage vectors however maximize electromagnetic torque during the non-commutation period. The proposed scheme results in unipolar switching that minimizes dv/dt leading to further reduction in torque ripple. Experimental validation on a laboratory prototype using a TMS320F28377S controller confirms the effectiveness of the proposed method.